Differences in game reading between selected and non-selected youth soccer players - Den Hartigh, R. J. R.; Van Der Steen, S.; Hakvoort, B.; Frencken, W. G. P.; Lemmink, K. A. P. M. (Journal of Sports Sciences, 2018)
Applying an established theory of cognitive development - Skill Theory - the current study compares the game-reading skills of youth players selected for a soccer school of a professional soccer club (n = 49) and their non-selected peers (n = 38). Participants described the actions taking place in videos of soccer game plays, and their verbalisations were coded using Skill Theory. Compared to the non-selected players, the selected players generally demonstrated higher levels of complexity in their game-reading, and structured the information of game elements - primarily the player, teammate and field - ?at higher complexity levels. These results demonstrate how Skill Theory can be used to assess, and distinguish game-reading of youth players with different expertise, a skill important for soccer, but also for other sports.